Molecular Epidemiology of an Outbreak of Febrile Gastroenteritis Caused by Listeria monocytogenes in Cold-Smoked Rainbow Trout - Miettinen, M. K. (American Society for Microbiology, 1999)
Febrile gastroenteritis in five healthy persons was associated with the consumption of vacuum-packed cold-smoked rainbow trout containing Listeria monocytogenes. L. monocytogenes isolates from the incriminated fish product lot and the stool samples were all of serotype 1/2a and were indistinguishable by pulsed-field gel electrophoresis employing AscI and SmaI.